Time‐course of clinical symptoms in young people at ultra‐high risk for transition to psychosis. Issue 6 (22nd July 2021) - Meneghelli, Anna; Cocchi, Angelo; Meliante, Maria; Barbera, Simona; Malvini, Lara; Monzani, Emiliano; Preti, Antonio; Percudani, Mauro
Abstract: Background: Ultra‐high risk (UHR) people are a heterogeneous group with variable outcomes. This study aimed at (a) estimating trajectories of response to treatment to identify homogeneous subgroups; (b) establishing the impact on these trajectories of known predictors of outcome in UHR subjects. Methods: Mixed models of growth curves and latent class growth analysis (LCGA) were applied to the 24‐item brief psychiatric rating scale (BPRS) to measure the response to treatment over 2 years in 125 UHR participants. Group differences were tested on sociodemographic variables and clinical indicators that are known to affect the outcome in UHR people. Results: BPRS scores decreased across all tested models, with a greater decrease for affective and positive symptoms than for all other dimensions of BPRS. Past admissions to the hospital for psychiatric reasons other than psychosis and the presence of a decline in premorbid functioning before the episode were associated with a slower decrease of BPRS score. LCGA identified three classes, one (82% of participants) with a progressive decrease in the BPRS scores, a second class with a moderate improvement (10%), and a third with no improvement (8%). Those in the 'no improvement' class had a higher chance of receiving a diagnosis of psychosis within the spectrum of schizophrenia. Conclusion: Most UHR individuals that are treated within a specialized service undergo substantial improvement in their psychopathology, but some seem resistant to the protocol of treatment and need close reevaluation within the first 12 months of treatment.